PERJUMPAAN DEKONSTRUKSI DERRIDA DAN TEOLOGI DOGMATIK:: SEBUAH ANALISIS DIALEKTIK DAN RESPONS APOLOGETIK - Belay, Yosep (STT-RAI Batam, 2024)
Abstract The dogmatic approach to theology in the modern era, the relationship between philosophy and theology is an important part that supports each other in a constructive direction. This is different when entering the postmodern era with its literary criticism. The foundation of dogmatic theology and philosophy based on language becomes a very radical criticism space by Derrida's deconstruction. Deconstructive criticism then has an impact on breaking logocentrism and metanarratives in all aspects so as to overhaul the structure of philosophy (logos) and dogmatic theology (Logos). This article seeks to read deconstruction criticism of philosophical and theological discourse, analyze its implications for dogmatic theology, then provide an apologetic response to deconstruction. The method used is descriptive qualitative by carefully analyzing various data from the